2008
DOI: 10.1016/j.bbapap.2008.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Seprase: An overview of an important matrix serine protease

Abstract: Seprase or Fibroblast activation protein (FAP) is an integral membrane serine peptidase, which has been shown to have gelatinase activity. Seprase has a dual function in tumour progression. The proteolytic activity of Seprase has been shown to promote cell invasiveness towards the ECM and also to support tumour growth and proliferation. Seprase appears to act as a proteolytically active 170-kDa dimer, consisting of two 97-kDa subunits. It is a member of the group type II integral serine proteases, which includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 99 publications
(178 reference statements)
3
108
1
5
Order By: Relevance
“…The localization of protease complexes at cell surface invadopodia is important in the processing of soluble factors, such as neuropeptide Y and certain chemokines (20). Furthermore, this process degrades local extracellular matrix components that are required for cell migration and matrix invasion during tumor invasion, angiogenesis and metastasis (21). Previous studies have revealed that seprase overexpression was evident in stromal fibroblasts and tumor cells in invasive breast, gastric, colonic and cervical carcinomas; however, it was absent or undetectable in all normal tissue cells, with the exception of cells involved in the early stages of wound healing (22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…The localization of protease complexes at cell surface invadopodia is important in the processing of soluble factors, such as neuropeptide Y and certain chemokines (20). Furthermore, this process degrades local extracellular matrix components that are required for cell migration and matrix invasion during tumor invasion, angiogenesis and metastasis (21). Previous studies have revealed that seprase overexpression was evident in stromal fibroblasts and tumor cells in invasive breast, gastric, colonic and cervical carcinomas; however, it was absent or undetectable in all normal tissue cells, with the exception of cells involved in the early stages of wound healing (22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast activated protein (FAP) and alpha smooth muscle actin (αSMA) are considered markers for cancer activated fibroblasts (CAFs) in many tumor types. FAP/seprase belongs to the family of plasma membrane-bound serine proteinases [19]. It is located at 2q23 and possesses gelatinolytic and collagenolytic activity as well as dipeptidyl peptidase activity, which have been implicated in matrix digestion and invasion [20].…”
Section: Discussionmentioning
confidence: 99%
“…It is located at 2q23 and possesses gelatinolytic and collagenolytic activity as well as dipeptidyl peptidase activity, which have been implicated in matrix digestion and invasion [20]. FAP is expressed in reactive cancer-associated fibrosis and granulation tissue in healing wounds while absent in normal adult tissues, and thus is a highly specific marker of CAFs [10,19,20]. Mesenchymal stem cells derived from human bone marrow are a source of TAFs in many tumor models and can express FAP.…”
Section: Discussionmentioning
confidence: 99%
“…DPP-2 is lysosomal (106), whereas DPP-4 and FAP␣ are both type II transmembrane proteins with a large C-terminal extracellular domain, a transmembrane domain, and a short cytoplasmic tail (107,108). These enzymes have the unique proteolytic ability to cleave N-terminal dipeptides from proteins with proline or alanine in the penultimate position.…”
Section: Dppsmentioning
confidence: 99%